Multiparametric Investigation of Chemically Treated and Untreated Sugarcane Bagasse Fiber-Reinforced Epoxy Composites With Wood Apple Shell as Filler: From Waste to Green Composite - Vinita Sharma; null Priyanka; Minakshi Verma; Deepak Kumar; Anu Gupta (International Journal of Polymer Science)
The development of green composites from agricultural residues is a paramount route in maintaining a sustainable environment. This has motivated us to carry out the manufacturing of hybrid fiber-reinforced biodegradable composites by employing sugarcane bagasse fiber and wood apple shell powder with epoxy via the hand lay-up process. Also, we treated the sugarcane bagasse fiber with alkaline NaOH solution and probed effect of varying weight percentage of wood apple shell as filler in steps of 0, 5, 10, and 15 resulting in a total of eight specimens corresponding to treated (TB0, TB5, TB10, and TB15) and untreated (UB0, UB5, UB10, and UB15) configurations. This has further facilitated to measure their mechanical, water absorption, thermal stability, and morphological aspects. We observe superior tensile and flexural strengths for TB10 having improvements of 94.29% and 32.60%, respectively, in comparison with TB0 at fixed 30 weight percentage of sugarcane bagasse fiber. These composites are further analysed in terms of stress–strain behaviors, where TB10 shows the maximum load-bearing capacity of 8.16 MPa under tensile test, while flexural test reveals the maximum stress of 22.90 MPa for TB10. Also, the impact test provides the highest impact energy of 4.2 and 3.7 J corresponding to treated (TB10) and untreated (UB10) cases of composites. In addition, we report an increase in water absorption as a function of filler loading for both treated and untreated specimens, whereas untreated composites exhibit a higher rate of water absorption with respect to treated ones at a fixed loading value. This study shows non-Fickian diffusion mechanism corresponding to all the samples. These outcomes can be comprehended in terms of the modulation in interfacial adhesion between polymer matrix and fiber and are well corroborated by scanning electron micrographs. Also, x-ray diffractograms represent that the alkaline-treated sugarcane bagasse fiber is found to be more crystalline (37.51% of crystallinity) than the untreated one (28.23% of crystallinity). Next, the maximum thermal stability using thermogravimetric analysis is obtained for the composite TB10 with 33% as its residue around 498°C due to the gradual breakdown of the primary constituents of the fiber. These findings have the potential to bring value-added applications in sectors of automation, interior designing, and packaging.